REGISTRATION OF MONITORY RIGHTS IS BASED ON THE REGULATION OF THE MINISTER OF AGRARIAN AND SPATIAL PLANNING/CHAIRMAN OF THE NATIONAL LAND AGENCY OF THE REPUBLIC OF INDONESIA NUMBER 5 OF 2020 CONCERNING ELECTRONIC INTEGRATED MONITORY RIGHTS SERVICES - Riza Zulfikar; Esty Oktavianty; Hadi Purnomo (Sean Institute, 2023)
The Electronic Mortgage Service is a service from the Ministry of ATR/BPN in facilitating services to the public by utilizing the development of information technology. Regulation of the Minister of Agrarian Affairs and Spatial Planning/Head of the National Land Agency Number 5 of 2020 concerning Electronically Integrated Mortgage Services which came into effect on April 8 2020. The formulation of the problems raised in this study are (1) What are the legal implications of electronic mortgage service regulations for PPAT and creditors? and (2) What are the legal remedies for problems that occur as a result of data input errors in electronic registration of mortgage rights. The research method used in this writing is a normative juridical research method, namely through literature study using a statutory approach related to problems, besides that the author also uses books related to problems. The conclusion that can be drawn in this study is that the mechanism for registering mortgage rights electronically against PPAT and creditors, for creditors there is a change in the creditor's task mechanism where creditors are required to apply for registration of mortgage rights directly through the electronic system and have the power to make notes to print mortgage rights. attached to the mortgage document. In addition, it has an impact on the timeliness of registration, which is seven days so that it can facilitate the granting of credit to debtors, while for PPAT, the PPAT's task is only to send APHT electronically in the system and provide guarantees for the correctness of the documents contained in the statement letter sent via the electronic system. Regarding input errors when registering HT-el at the National Land Office, not only from the network system factor, but the human factor, namely human negligence which results in being unable to upload documents or access applications, and document factors such as data input errors when making the deed carried out by the PPAT.